2023
DOI: 10.3390/ijms24065509
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of Recombinant Bacille Calmette-Guérin Strain VPM1002 and Its Derivatives in a Goat Model

Abstract: A more effective vaccine against tuberculosis than Bacille Calmette-Guérin (BCG) is urgently needed. BCG derived recombinant VPM1002 has been found to be more efficacious and safer than the parental strain in mice models. Newer candidates, such as VPM1002 Δpdx1 (PDX) and VPM1002 ΔnuoG (NUOG), were generated to further improve the safety profile or efficacy of the vaccine. Herein, we assessed the safety and immunogenicity of VPM1002 and its derivatives, PDX and NUOG, in juvenile goats. Vaccination did not affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Fewer lymphocytes than in other models (76)(77)(78). Diagram of a general pulmonary tuberculous granuloma.…”
Section: Necrosis Mineralisation Fibrosis Mngcs Afb Cavitary Lesions ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Fewer lymphocytes than in other models (76)(77)(78). Diagram of a general pulmonary tuberculous granuloma.…”
Section: Necrosis Mineralisation Fibrosis Mngcs Afb Cavitary Lesions ...mentioning
confidence: 99%
“…Goat TB closely resembles bovine and human TB in terms of immune response and pathological characteristics. They exhibit comparable patterns of disease progression, with a predominant anatomical localisation within the respiratory tract and the formation of caseous granulomas ( 77 , 107 ). In addition, goats demonstrate notable similarities in the anatomical structure of their respiratory tract, as well as a comparable size and body weight to that of humans ( 107 ).…”
Section: Comparative Pathology Of Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, one report suggested that BCG has only a limited protective efficacy after challenge with M. caprae ( 259 ). More recent advanced goat models using video endoscopy for infection via intrabronchial spray inoculation ( 283 ) have demonstrated the relevance and suitability of goats for vaccine studies using BCG and new clinical candidates ( 284 , 285 ). Considering that BCG is the only licensed vaccine against TB it still remains the gold standard when testing new vaccine concepts.…”
Section: Large Animal Modelsmentioning
confidence: 99%